2012
DOI: 10.1093/infdis/jis184
|View full text |Cite
|
Sign up to set email alerts
|

Drug Screen Targeted at Plasmodium Liver Stages Identifies a Potent Multistage Antimalarial Drug

Abstract: Plasmodium parasites undergo a clinically silent and obligatory developmental phase in the host’s liver cells before they are able to infect erythrocytes and cause malaria symptoms. To overcome the scarcity of compounds targeting the liver stage of malaria, we screened a library of 1037 existing drugs for their ability to inhibit Plasmodium hepatic development. Decoquinate emerged as the strongest inhibitor of Plasmodium liver stages, both in vitro and in vivo. Furthermore, decoquinate kills the parasite’s rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 31 publications
1
97
0
Order By: Relevance
“…To address both of these issues, we asked whether the likelihood of mitosis in the host cell would be similarly altered at 24 h in cells harboring nondeveloping parasites that had undergone normal invasion. To block parasite development as early as possible after invasion, we treated cells with decoquinate (DCQ), a cytochrome bc 1 inhibitor and potent antimalarial (23,24) that is active against very early liver stages, such that a 6-h treatment from 2 to 8 h after sporozoite addition prevents parasite growth but does not lead to parasite elimination (25). A representative image of such a DCQ-treated parasite in a metaphase HepG2 cell 24 h postinfection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To address both of these issues, we asked whether the likelihood of mitosis in the host cell would be similarly altered at 24 h in cells harboring nondeveloping parasites that had undergone normal invasion. To block parasite development as early as possible after invasion, we treated cells with decoquinate (DCQ), a cytochrome bc 1 inhibitor and potent antimalarial (23,24) that is active against very early liver stages, such that a 6-h treatment from 2 to 8 h after sporozoite addition prevents parasite growth but does not lead to parasite elimination (25). A representative image of such a DCQ-treated parasite in a metaphase HepG2 cell 24 h postinfection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One strategy used an in silico virtual screening approach to identify novel type II fatty acid biosynthesis inhibitors with multistage antimalarial activity (45). Other strategies have focused on phenotypic-based screens for the discovery of new lead molecules with liver-and blood-stage activities (7,(46)(47)(48)(49). The use of these phenotypic-based screens has contributed to the identification of various preclinical small-molecule compounds such as imidazopyrazines (e.g., KAI407), imidazolopiperazine (e.g., KAF156), Plasmodium phosphatidylinositol-4-OH kinase inhibitors, spiroindolones (e.g., KAE609), P. falciparum P-type ATPase 4 inhibitors, and DDD107498, a translation elongation factor 2 inhibitor (50-54).…”
Section: Challenges and Current State Of Malaria Drug Developmentmentioning
confidence: 99%
“…To specifically address the targeting of the mitochondrial ETC via inhibition of the cytochrome bc 1 complex, we assessed the susceptibility of P. falciparum Dd2-yDHODH transgenic parasites to screening actives with and without cotreatment with proguanil, a dihydrofolate reductase inhibitor. It was previously shown that proguanil restores the sensitivity of transgenic parasites, P. falcip- arum Dd2-yDHODH, to cytochrome bc 1 complex inhibitors (24,26), thereby providing a method to identify compounds that target this enzyme complex (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%